Performance improvement of an HVAC system using water and ethylene glycol-based ternary hybrid nanofluids with green-synthesized Fe-Cu-Fe2O3 nanoparticles - Maryam Rabiu Aliyu; Huzaifa Umar; Michael Adedeji; Ali Shefik; Dilber Uzun Ozsahin; Mustafa Dagbasi (PLoS ONE, 2025)
This study investigates the potential of water and ethylene glycol-based ternary nanofluids, enhanced with both chemically and green synthesized Fe-Cu-Fe2O3 nanoparticles, to improve the performance of a heating, ventilation and air conditioning (HVAC) system. It also compares the effectiveness of the two synthesis methods, addressing the current research gap in the practical application of green-synthesized nanofluids in HVAC systems. Two sets of nanoparticles were synthesized using chemical and eco-friendly methods and dispersed in a base fluid of water and ethylene glycol (EG) at varying concentrations of 0%, 50%, and 75% EG with various nanoparticle mixture ratios. The prepared ternary nanofluids were used to evaluate the thermal performance of the heater in an air-handling unit (AHU). Experimental data on the thermophysical properties of the nanofluid at the different mixture ratios were incorporated into a numerical model simulating the AHU operating in a Mediterranean climate. Results show that the nanofluids significantly enhance system performance, with the 1Fe: 2Cu: 1Fe2O3 nanoparticle mixture ratio offering the best balance between efficiency and operational stability. The heat transfer rates were improved by up to 20% in summer and 15% in winter compared to the base fluid. In addition, the mixture ratio achieved optimal exergy efficiency, peaking at 98% during winter operation and 96% during summer. Comparative analysis also shows that the ternary nanofluids containing the chemical-synthesized nanoparticles (CSNTNF) perform only slightly better than the nanofluids containing the green-synthesized nanoparticles (GSNTNF). This suggests that GSNTNF is a suitable replacement for the CSNTNF, considering the environmental benefits.